Penyediaan Toko Digital Pasar Rabu Tani untuk Pelaku Usaha Pangan Skala Kecil di Kota Padang - Eli Ratni; Virtuous Setyaka; Donny Eros (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2021)
Pasar Rabu Tani (PRT) is an online media for buying and selling transactions between producers and consumers of food needs, in the form of a digital shop on the site https://pasarrabutani.com/. PRT created an alternative form of the market by uniting small-scale food business actors in a cooperative called the Koperasi Pemasaran Mandiri dan Merdeka. Due to the Covid-19 pandemic, PRT must shift the marketing system from conventional direct meetings between producers and consumers to a contextual system where producers and consumers cannot have direct meetings. Digital stores are one of the solutions for market media during a pandemic by utilizing information and communication technology products. The management of this market in terms of buying and selling is carried out by special operators who act as website managers, data administrators, and delivery personnel. The methods used were enhancing product quality by producers, socializing the online shopping system to consumers, and assisting operators of PRT in running a business. The digital strategy in the marketing and transactions of food products makes it easy for managers to obtain a database of potential producers and products and a database of possible consumer performance, both from within and outside West Sumatra. Digital stores that are displayed online, of course, reach consumers without space and time limits, which affects increasing producer income.